2006
DOI: 10.1016/j.ejcnurse.2005.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Changes Following Acute Myocardial Infarction: Patients Perspectives

Abstract: The study highlights the need for the development of primary care services and cardiac rehabilitation programmes to support patients as well as providing information to families to reduce anxiety and fear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
100
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 22 publications
8
100
1
6
Order By: Relevance
“…The present study also revealed that partners rarely received oral or written information about sexual function and coexistence after an MI. It is important that the partners of MI patients become involved, as it would increase their understanding of the situation, reduce the risk of overprotection 22 , and make both themselves and the patient aware of the relatively small risk of sexual intercourse triggering another MI 23 . Counselling should therefore focus on encouraging patients to live a physically active life and not to abstain from sexual activity 6 .…”
Section: Results Issuesmentioning
confidence: 99%
“…The present study also revealed that partners rarely received oral or written information about sexual function and coexistence after an MI. It is important that the partners of MI patients become involved, as it would increase their understanding of the situation, reduce the risk of overprotection 22 , and make both themselves and the patient aware of the relatively small risk of sexual intercourse triggering another MI 23 . Counselling should therefore focus on encouraging patients to live a physically active life and not to abstain from sexual activity 6 .…”
Section: Results Issuesmentioning
confidence: 99%
“…The participants in Kristofferzon et al's study (Kristofferzon et al, 2007) felt that the network was generally supportive but they often experienced communication problems when they interacted with their network. Overprotection by family members was also identified as a source of frustration and aggravation for participants (Condon and McCarthy, 2006). This suggested that participants valued the opportunity to self-manage their recovery.…”
Section: Importance Of Ongoing Needs and Support During Self-managingmentioning
confidence: 97%
“…The findings highlighted information needs and access to multimodal forms of education, discharge planning and planning for contingencies after hospital discharge and facilitating support resources as important areas for service improvement. Another study (Condon and McCarthy, 2006) found that the difficulties encountered by participants six weeks following hospital discharge were due to the implementation of too many life style changes at once as well as the lack of professional help in the community to support them to make lifestyle changes. In Gregory et al's study An unmet need for reliable information was identified by ten female survivors of first-time myocardial infarction in Australia .…”
Section: Importance Of Ongoing Needs and Support During Self-managingmentioning
confidence: 99%
See 1 more Smart Citation
“…In part, the labelling of such a risk factor as a disease potentially removes the person from the process as 'diseases' are objective classifications imposed by a health professional, thereby potentially dislocating the person from their broader social context 12 . In addition, the perceptions of patients needing to make lifestyle adaptations needs to be understood 13 . Prevention should therefore engage individuals, families and communities on a wholeof-lifespan basis, with context-specific strategies tailored to the presenting need.…”
mentioning
confidence: 99%